Hospice nurse identification of comfortable and difficult discussion topics: Associations among self-perceived communication effectiveness, nursing stress, life events, and burnout. Issue 10 (October 2019) - Clayton, Margaret F.; Iacob, Eli; Reblin, Maija; Ellington, Lee
Highlights: Hospice nurses perceive themselves as effective communicators. Most hospice nurses want addition communication skills training. Self-perceived communication effectiveness is associated with burnout and stress. Challenging communication topics such as Denial can be identified by hospice nurses. Addressing self-identified communication challenges may optimize end-of-life care. Abstract: Objective: To assess hospice nurses' self-perceived communication effectiveness, identify comfortable and difficult discussion topics, and explore associations between self-perceived communication effectiveness, burnout, nursing stress, and life events. Methods: 181 nurses completed self-report measures, then listed comfortable and/or difficult patient and caregiver discussion topics. Results: Nurses were generally experienced (median 9 years, range <1–46 as a registered nurse; median 3 years, range <1–23 as a hospice nurse), reporting overall Effective/Very Effective communication skills (85.6%); 70% desired more communication training. As nursing stress increased perceived overall communication effectiveness decreased (rs = −0.198; p 0.012). As burnout increased overall effectiveness (rs = −0.233; p 0.002) and effectiveness with difficult topics (rs = −0.225; p 0.003) decreased. Content analysis revealed 9 categories considered both comfortable and difficult to discuss; contextual comments provided fuller explanation (e.g. providing general information on the Dying Process was comfortable, discussing Dying process during patient death was difficult). Seven additional categories (e.g. Denial) were deemed uniquely difficult. Conclusion: Hospice nurses perceive themselves as effective communicators, yet want additional training. Perceived communication effectiveness is associated with burnout and stress. Practice implications: Communication training that focuses on contextually grounded topics identified by participants may optimize communication between hospice nurses, patients and caregivers.